Managing Director's Statement to the Development Committee. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
A Statement from the Managing Director of the International Monetary Fund, Rodrigo de Rato, for the Committee's seventy-third meeting to be held in Washington, D.C., on Sunday, April 23, 2006.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet